y(y-6)=0

Simple and best practice solution for y(y-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(y-6)=0 equation:


Simplifying
y(y + -6) = 0

Reorder the terms:
y(-6 + y) = 0
(-6 * y + y * y) = 0
(-6y + y2) = 0

Solving
-6y + y2 = 0

Solving for variable 'y'.

Factor out the Greatest Common Factor (GCF), 'y'.
y(-6 + y) = 0

Subproblem 1

Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0

Subproblem 2

Set the factor '(-6 + y)' equal to zero and attempt to solve: Simplifying -6 + y = 0 Solving -6 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + y = 0 + 6 y = 0 + 6 Combine like terms: 0 + 6 = 6 y = 6 Simplifying y = 6

Solution

y = {0, 6}

See similar equations:

| 5y^2=3y-7 | | 2b-3=2b-7 | | 27=p | | -4(6x-2)+3=-24x+11 | | 27=x | | 5-3(-4)=-7 | | 5=3b-8b | | 10.7=-d+43 | | 11x+4=5(2x-1)+9 | | 13-r=-3(-r+1) | | -3(4x+3)=-9 | | 2b-3=2b-6 | | 2a+3(a+4)= | | 8(x+2)-8=17-3x-9+11x | | 60t^4-4at^2+12t= | | (2x-3)(4x-2)= | | 0.33333333333x+10=55 | | x=2x^2+7x+9 | | -a/25=8 | | -4+9(x-2)=16x+3-7x | | .45x+.05(14-x)=.10(-25) | | -8-11=-5x+23 | | 0.80.2=x | | q^2+q-20=0 | | -(6xy-12)+3(5xy+8)= | | (6x+5)-1.3=-1.9 | | 0.33x+10=55 | | 14p^3q^3-21p^2q^2+35pq= | | 400-5x=322-3x | | 2(7)+6+5(7)=55 | | 8789-3434=876x | | -11-r=4(r-4) |

Equations solver categories